Poučevanje slovenskega jezika za Poljake v kognitivnem pristopu (izbrani vidiki) - Będkowska-Kopczyk, Agnieszka (Slavia Centralis, 2020)
Teaching Poles Slovene Language using a cognitive approach (selected aspects) Cognitive linguistics is based on the assumption that language reflects human psychological processes. Meaning, as a subject of constant negotiation among people, is not just the conceptual content of the expression, it is the way in which the content is construed in a certain speaking context. It is influenced by both the structure of a given language and the vision of the world of its users. This view influences the cognitive linguistic approach to foreign language acquisition. This paper presents a cognitive approach to language and foreign language teaching; the theoretical section is followed by examples of Slovene expressions which are a conceptual challenge for Polish students of that language.